The cat who turned on and off - Braun, Lilian Jackson (Jove Books, 1986)
The team of Koko, the brilliant Siamese cat, and Qwilleran, the reporter with the perceptive moustache, is back in action--with an adorable female Siamese, Yum Yum, added to the household. When Qwilleran decides to do a feature story on Junktown, he gets more than he bargained for. Not the dope den he anticipated, Junktown is a haven for antique dealers and collectors--as strange a lot as the crafty reporter has ever encountered. When a mysterious fall ends the career--and the life--of one of Junktown's leading citizens, Qwilleran is convinced it was no accident. But, as usual, it takes Koko to prove he's right. Qwilleran and Koko, the beautiful Siamese cat, are back on the mystery beat. When a mysterious fall ends the life of one of Junktown's leading citizens, Qwilleran is convinced it was no accident. And Koko is about to prove him right.